Dificuldades de ensino e aprendizagem em matemática no ensino superior na perspectiva de docentes e discentes - de Oliveira Lopes Vieira, Daniela; Drigo, Maria (Série-Estudos, 2022)
This article aims to contribute to the understanding of possible causes of teaching and learning difficulties, from the perspective of teachers and students, respectively, in matters that involve mathematical knowledge, in college education. Specifically, it seeks to identify the probable reasons for learning difficulties in mathematics, on the part of the student; identify the probable reasons for difficulties in teaching mathematics, on the part of the teacher; explain aspects about mathematics and its teaching and conceptions, especially those linked to mathematical knowledge, which can support the teaching practices in progress. The reflections involve data from interviews carried out with professors and students from three universities, one of each modality − public, private, and community −, in the region of Sorocaba, SP. We found that practices with exposure of matters, examples, and problem solving predominate, as well as the conception that mathematics is a knowledge in which the linearization of matters prevails.